PKM PELATIHAN PENULISAN BUKU BAGI GURU MTS ARIFAH GOWA - Adnan Adnan; Andi Asmawati Azis; Muliana GH; Andi Farida Arsal; Suhardi Aldi (Jurusan Matematika FMIPA UNM, 2024)
Abstract. This community service activity aims to enhance book writing skills among teachers. It is essential for teachers to develop their professionalism, one way being through book writing activities. The book writing training at MTs Arifah Gowa is designed to help teachers overcome limitations in producing scientific writings and textbooks, as well as to encourage them to continuously develop their professionalism and competence. The training methods used include lectures, question-and-answer sessions, and discussions, focusing on various aspects of book writing, from idea generation to the publishing process. The results of this training show that teachers feel more confident and motivated to write and understand the importance of literacy in education. This training not only provides a better understanding of book writing techniques but also helps teachers integrate research into their teaching materials, improving the quality of teaching and literacy in schools. The survey results from teachers indicate that this training contributes positively to the development of literacy and writing skills among teachers at MTs Arifah Gowa. Keywords: Book writing training, writing skills, literacy, teacher professionalism, teaching quality